Identification of fine antigenic epitopes of Tamdy virus glycoprotein Gn fragment and establishment of ELISA detection method - Yujiao Fu; Liping Liu; Beibei Zhang; Xiaoshan Chao; Junxia Jin; Ying Wang; Juntao Ding (Parasites & Vectors)
Abstract Background Tamdy virus (TAMV) was first isolated in Uzbekistan and Turkmenistan. In 2018, it was found in China, marking its entry into the molecular research era. TAMV is linked to febrile diseases, but its epidemiology and spillover risks are poorly understood, necessitating urgent molecular research and detection method development. Methods The secondary structure of TAMV glycoprotein Gn was predicted, and the results showed that it had rich antigenic epitopes. According to the predicted results, glycoprotein Gn was divided into 46 truncated 16-peptides by modified synthetic peptide method, and the antigenicity of 46 truncated 16-peptides was verified by western blotting analysis. Results The results showed that P8, P9, P24, P25, P28, P29, and P39 had antigenicity. Subsequently, the seven positive 16-peptide sequences with antigenicity were truncated to form 8-peptide sequences with an overlap of seven amino acids. After analysis with the same method, eight fine antigenic epitopes E1 (58VINSTLDH65), E2 (65HVGSWGMP72), E3 (68SWGMPVTT75), E4 (187IRNQPFKS194), E5 (195FNVEVQ200), E6 (226AVVEHH231), E7 (228VEHHGNKA235), and E8 (310RGGRR314) were identified, all of which were located on the three-dimensional surface of glycoprotein Gn and were highly conserved in different TAMV strains. Conclusions Eight precise epitopes were identified, and an indirect ELISA method based on fusion multiepitope peptide (r-Gn-MEPX2) was developed and implemented, featuring high sensitivity, accuracy, and specificity. Graphical Abstract